Service-based negotiation for advanced collaboration in enterprise networks - Coutinho, C.; Cretan, A.; Ferreira da Silva, C.; Ghodous, P.; Jardim-Goncalves, R. (Journal of Intelligent Manufacturing, 2016)
Information systems support organisations to achieve greater efficiency by automating their activities. Nowadays, in the actual competitive and global business context, the advent of enterprise networking has been challenging collaboration, coordination and continuous interactions among dissimilar information systems to adapt and improve them. Sustainability of interoperability among heterogeneous systems regarding sharing information and knowledge in a collaborative dynamic environment is hard to achieve and maintain. This paper proposes a service-based negotiation framework for advanced collaboration in enterprise networks, as a solution to improve the sustainability of interoperability within enterprise information systems. Validation in industrial scenario is presented and discussed.